2007
DOI: 10.1053/j.gastro.2007.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Identification of a Multilineage Progenitor in Murine Stomach Epithelium

Abstract: Background and Aims-Epithelial stem cells in the stomach are responsible for constant renewal of the epithelium through generation of multiple gastric cell lineages that populate the gastric glands. However, gastric stem or progenitor cells have not been well-characterized due to the lack of specific markers that permit their prospective recognition. We identified an intestinal promoter that is active in a rare subpopulation of gastric epithelial cells and investigated whether these cells possess multilineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
135
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 37 publications
5
135
0
Order By: Relevance
“…Infusion of IFN-␥ into wildtype mice was further shown to induce expansion of the mucous neck cell compartment in vivo, probably by triggering the deregulated proliferation of this cell type (54). In a study investigating a rare progenitor cell type of the antral gland by lineage tracing, Qiao et al (55) observed that these cells have multilineage potential (i.e., they give rise to all lineages of the antral gland) and that they multiply in response to IFN-␥. In our own previous study investigating the response of the three terminally differentiated gastric epithelial lineages to Helicobacter infection in vivo using a laser capture approach, we found that the mucus-producing pit cell responds strongly to infection (56) by up-regulating numerous known target genes of the IFN-␥ signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of IFN-␥ into wildtype mice was further shown to induce expansion of the mucous neck cell compartment in vivo, probably by triggering the deregulated proliferation of this cell type (54). In a study investigating a rare progenitor cell type of the antral gland by lineage tracing, Qiao et al (55) observed that these cells have multilineage potential (i.e., they give rise to all lineages of the antral gland) and that they multiply in response to IFN-␥. In our own previous study investigating the response of the three terminally differentiated gastric epithelial lineages to Helicobacter infection in vivo using a laser capture approach, we found that the mucus-producing pit cell responds strongly to infection (56) by up-regulating numerous known target genes of the IFN-␥ signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…From ultrastructural observations in the isthmic region of human stomach, Karam et al [100] have suggested that perhaps the stem cells are so-called mini-granule cells, cells with minute, dense or cored, secretory granules, somewhat akin to the granule-free cells found in the mouse. In the isthmic region of mouse antral glands, a population of LRCs have been found expressing a protein more characteristic of the small intestine, villin [101]. Lineage tracing from villin-positive cells using Cre recombinase suggested these cells were multipotential, but generally they were proliferatively very quiescent unless exposed to inflammatory cytokines.…”
Section: Digestive Tractmentioning
confidence: 99%
“…In samples IM7 and IM8, the level of mucin expression, either intestinal or gastric type, was low, whereas that of Villin1 (VIL1) was high. Although VIL1 is known as an enterocyte marker, it is also expressed in gastrointestinal stem/progenitor cells (18). Accordingly, samples IM7 and IM8 may have been derived from lesions that persisted in a less-differentiated state rather than having undergone transdifferentiation.…”
mentioning
confidence: 99%